2018
DOI: 10.1117/1.jmi.5.4.046003
|View full text |Cite
|
Sign up to set email alerts
|

Application of unsupervised learning to hyperspectral imaging of cardiac ablation lesions

Abstract: Atrial fibrillation is the most common cardiac arrhythmia. It is being effectively treated using the radiofrequency ablation (RFA) procedure, which destroys culprit tissue and creates scars that prevent the spread of abnormal electrical activity. Long-term success of RFA could be improved further if ablation lesions can be directly visualized during the surgery. We have shown that autofluorescence-based hyperspectral imaging (aHSI) can help to identify lesions based on spectral unmixing. We show that use of k-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…To date, we have confirmed that Auf-HSI can reveal ablation lesions made in the left atrium of large mammals, including pigs, sheep, and cows 9 , as well as in donated human heart tissue 10 . The dimensions and the shape of the lesions delineated by Auf-HSI were in perfect agreement with the conventional post-ablation staining methods such as TTC [10][11][12][13][14] . These promising bench findings have led to our ongoing efforts to incorporate Auf-HSI technology into a percutaneous imaging catheter 11,15,16 .…”
supporting
confidence: 66%
See 1 more Smart Citation
“…To date, we have confirmed that Auf-HSI can reveal ablation lesions made in the left atrium of large mammals, including pigs, sheep, and cows 9 , as well as in donated human heart tissue 10 . The dimensions and the shape of the lesions delineated by Auf-HSI were in perfect agreement with the conventional post-ablation staining methods such as TTC [10][11][12][13][14] . These promising bench findings have led to our ongoing efforts to incorporate Auf-HSI technology into a percutaneous imaging catheter 11,15,16 .…”
supporting
confidence: 66%
“…The important practical implication of our studies is the dramatically reduced amount of spectral information needed to reveal the ablated tissue. In the past, we have attempted to approach this issue mathematically 12 , 42 . In those studies, we used combinatorial tools to screen all possible wavelength combinations from the Auf-HSI datasets for a minimal number of wavelengths that can still provide good-quality outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…That is why we use term 'hyperspectral' when describing our findings. Our recent post-acquisition analysis of continuous spectra from these hyperspectral datasets revealed the most informative wavelengths, allowing us to consider use of fewer and wider bands [30,38]. In order not to confuse our readers by juggling between the two terms while referring to our previous publications and bench datasets, we decided to continue to refer to this technology as hyperspectral, although the final iteration of the clinical device is most likely to be classified as 'multispectral'.…”
Section: Multispectral and Hyperspectral Imagingmentioning
confidence: 99%
“…[16][17][18] Previously, our research group demonstrated the ability of a machine learning approach, i.e., a convolutional neural network (CNN), to detect fibrosis in FCM images taken in a beating heart in situ. 19,20 Other previous studies explored machine learning for cardiac ablation lesion quantification 21 and diagnosis of ischemic heart disease. 17,22 Here, we introduced a novel system for broad-spectrum LSS for applications in cardiology and cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%